Characterization and sorting of flow cytometric populations in human semen. (3rd April 2014) - Marchiani, S.; Tamburrino, L.; Olivito, B.; Betti, L.; Azzari, C.; Forti, G.; Baldi, E.; Muratori, M.
Summary Human semen is a complex biological matrix. It contains mature spermatozoa, immature germ cells, residual apoptotic bodies and, in some cases, epithelial cells and leucocytes. Hence, one of the challenges in applying flow cytometry in spermatology is the correct recognition of spermatozoa and their separation from signals of other semen cells/elements. In this study, we show that semen spermatozoa are included in a well‐defined, flame‐shaped FSC/SSC region (FR), by demonstrating that the count of the spermatozoa contained in such region overlaps that obtained by microscopy in the same samples. In FR, nuclear staining of semen samples reveals three different populations: unstained, brighter and dimmer. Unstained elements were previously characterized as apoptotic bodies of testis origin and the brighter elements represent the majority of semen spermatozoa, whereas the composition and the origin of the population with a lower nuclear staining is less clear, albeit we have previously shown that all the elements constituting it are positive for TUNEL. In this study, we sorted all the elements contained in FR region and demonstrated that the dimmer elements are spermatozoa. To further characterize dimmer spermatozoa, we evaluated apoptotic caspases and chromatin immaturity, the latter detected by aniline blue (AB) and chromomycin A (CMA3) staining. We found that caspases were much more expressed in the dimmer spermatozoa (71.4 ± 18.8%) than in the brighter (46.7 ± 15.1%), whereas similar amounts of spermatozoa with chromatin immaturity were found in both populations (brighter, AB: 48.2 ± 19.5%; CMA3: 48.5 ± 20.4% and dimmer, AB: 43.4 ± 19.8%; CMA3: 36.1 ± 18.0%). Hence, the role of apoptosis in generating dimmer spermatozoa and their DNA fragmentation appears clear, whereas the involvement of defects during the chromatin packaging remains elusive.